Protein binding of clindamycin in vivo by means of intravascular microdialysis in healthy volunteers. (10th May 2021) - Wulkersdorfer, Beatrix; Wicha, Sebastian G; Kurdina, Elizaveta; Carrion Carrera, Stephan F; Matzneller, Peter; Al Jalali, Valentin; Vossen, Matthias G; Riesenhuber, Sonja; Lackner, Edith; Dorn, Christoph; Zeitlinger, Markus
Abstract: Objectives: The efficacy of an anti-infective drug is influenced by its protein binding (PB), since only the free fraction is active. We hypothesized that PB may vary in vitro and in vivo, and used clindamycin, a drug with high and concentration-dependent PB to investigate this hypothesis. Methods: Six healthy volunteers received a single intravenous infusion of clindamycin 900 mg. Antibiotic plasma concentrations were obtained by blood sampling and unbound drug concentrations were determined by means of in vivo intravascular microdialysis (MD) or in vitro ultrafiltration (UF) for up to 8 h post dosing. Clindamycin was assayed in plasma and MD fluid using a validated HPLC-UV (ultraviolet) method. Non-linear mixed effects modelling in NONMEM ® was used to quantify the PB in vivo and in vitro . Results: C max was 14.95, 3.39 and 2.32 mg/L and AUC0–8h was 41.78, 5.80 and 6.14 mg·h/L for plasma, ultrafiltrate and microdialysate, respectively. Calculated ratio of AUCunbound /AUCtotal showed values of 13.9%±1.8% and 14.7%±3.1% for UF and microdialysate, respectively. Modelling confirmed non-linear, saturable PB for clindamycin with slightly different median (95% CI) dissociation constants ( K d ) for the alpha-1 acid glycoprotein (AAG)–clindamycin complex of 1.16 mg/L (0.91–1.37) in vitro versus 0.85 mg/L (0.58–1.01) in vivo . Moreover, the estimated number of binding sites per AAG molecule was 2.07 (1.79–2.25) in vitro versus 1.66 in vivo (1.41–1.79). Conclusions: Concentration-dependent PB was observed for both investigated methods with slightly lower levels of unbound drug fractions in vitro as compared with in vivo .